Effect Of Sintering Temperature On Structural Properties Of LiMnPO4 Cathode Materials Obtained By Sol–Gel Method - K., Rajammal; Sivakumar, Dhar Malingam; Navaneethan, Duraisamy; K., Ramesh; S., Ramesh (Springer, 2016)
Nanostructured LiMnPO4 cathode materials were successfully achieved by sol–gel route with the aid of oxalic acid and nitric acid. The effects of sintering temperatures on structural properties especially strain and crystallite size were analysed. The structural crystallinity and average particle sizes (42–77 nm) of LiMnPO4 are significantly varied with respect to calcination temperatures. LiMnPO4 obtained at 700 C exhibits superior electrochemical performance among the samples. It delivered initial discharge capacity of 103.4 mAh g-1 at 0.05 C. These results revealed that the sol–gel technique could be favourable method to produce nanosized LiMnPO4 as a cathode material for lithium ion batteries via optimizing calcination temperatures.